Ni-co alloys electrodeposited in stainless steel for supercapacitors electrodes - Silva,R. P. (2013)
The development of electric energy storage devices with high power density has become one of the most challenging research areas in a wide range of applications. In this context, electrochemical supercapacitors are attracting great attention due to their high potential density, fast charge-discharge cycles and high number of life cycles. In the present work, Ni-Co nanostructured films were produced by electrodeposition technique in order to form a porous dendritic structure with enhanced surface area. The electrochemical behaviour of the deposited films was studied by charge-discharge experiments. The Ni-Co dendritic films electrodeposited at current densities i1 = -4 mA cm-2 and i2 = -30 mA cm-2 display a specific capacitance of 215 F g-1. The capacitance loss is about 33 % after 6000 charge-discharge cycles.